Filipino female juvenile delinquents an exploratory study of their level of intelligence, personality, and attitudes towards the self and selected social figures - Carlota, Annadaisy J. (Philippine Journal of Psychology, 1982)
The article describes the intellectual and personality characteristics of Filipino female juvenile delinquents as well their attitudes towards their self and selected social figures. The participants of the study included 31 delinquents who were matched with an equal number of non-delinquent controls on the variables of age, sex and socio-economic status. All participants were administered the Raven's Standard Progressive Matrices (RSPM), the High School Personality Questionnaire (RSPQ), the Rohde Sentence Completion Test (RSCT) and selected cards form the Thematic Apperception Test (TAT). The results showed that delinquents obtained significantly lower intelligence scores on two indicators, namely, The RSPM and the intelligence factor of the HSPQ. Testing with the HSPQ also revealed that delinquents, compared to non-delinquents are: less moralistic, more inclined to disregard rules, and more impenitent; critical of people, cool and aloof in their interpersonal interaction; inclined to disregard their social obligations; more emotionally undemonstrative. Finally, analysis of the data from the RSCT and TAT indicate that more delinquents display a strong abasive attitude towards the self. They are also more critical of their abilities and their behaviors. Fewer delinquents have a positive attitudes towards the members of their families and towards peers, of the same and the opposite sex. An attempt to explain the findings from a social-learning point of view was undertaken.